Phenolated Alkali Lignin/Magnetite Composite as an Adsorbent for Methyl Violet 6B in Wastewater: 10.32526/ennrj/22/20230256 - Rodil, Mary Sheenalyn P.; Sacdalan, Corazon D.; Robero, Rissabell R.; Salinas, Maria Evytha L.; Santander, Trixie N. (Environment and Natural Resources Journal, 2024)
Methyl violet 6B (MV6B), found in wastewater, poses hazardous effects to aquatic ecosystems and human health; therefore, it must be removed immediately. In response, this study pioneered the development of a dye adsorbent by incorporating phenolated alkali lignin (PAL) into magnetite (Fe3O4), offering a solution for MV6B removal. Lignin was extracted from coconut husk through alkali extraction, chemically modified using phenolation, and integrated onto the magnetite surface. SEM and FTIR spectroscopy were used to characterize the adsorbent, and various parameters were optimized, along with evaluations of the adsorption kinetics and isotherm models, as well as the adsorbent’s reusability. PAL was successfully deposited onto the magnetite based on the characterization. The experimental results revealed that the optimal conditions for the removal of MV6B using PAL/Fe3O4 composite are pH 4, a temperature of 313 K, a dosage of 0.10 g PAL/Fe3O4 per 15 mL of MV6B, and a contact time of 150 minutes. MV6B’s equilibrium removal rate was 95.1%, with an adsorption capacity at equilibrium of 6.42 mg/g. The adsorption of MV6B followed a pseudo-second-order kinetic model and the Freundlich model isotherm. A thermodynamic study showed that the adsorption process was spontaneous and exothermic. PAL/Fe3O4 was highly reusable after three cycles without the need for desorption. Hence, this study has demonstrated that the PAL/ Fe3O4 adsorbent is practical, economical, and efficient for wastewater treatment.